2012
DOI: 10.1039/c2ay25511a
|View full text |Cite
|
Sign up to set email alerts
|

Well-redispersed ceria nanoparticles: Promising peroxidase mimetics for H2O2 and glucose detection

Abstract: Well-redispersed ceria nanoparticles (CeO 2 NPs) were synthesized by a simple hydrothermal method. The prepared CeO 2 NPs exhibited excellent catalytic activity towards classical peroxidase substrate 3,3,5,5-tetramethylbiphenyl dihydrochloride (TMB$2HCl) in the presence of H 2 O 2 , based on which a colorimetric method that is highly sensitive and selective was developed for glucose detection. The composition, structure, morphology and peroxidase-like catalytic activity of CeO 2 NPs are investigated in detail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(148 citation statements)
references
References 35 publications
3
142
0
3
Order By: Relevance
“…10,[43][44][45][46] Although the mechanisms of these activities were not thoroughly studied and fully understood, one could hypothesize that the properties resemble the mechanism of catalytic activities observed in nonbiological systems. These enzyme-mimetic properties make CeONPs useful in biotechnology and therapeutics.…”
Section: The Multi-enzyme Mimetic Activities Of Ceonpmentioning
confidence: 99%
See 1 more Smart Citation
“…10,[43][44][45][46] Although the mechanisms of these activities were not thoroughly studied and fully understood, one could hypothesize that the properties resemble the mechanism of catalytic activities observed in nonbiological systems. These enzyme-mimetic properties make CeONPs useful in biotechnology and therapeutics.…”
Section: The Multi-enzyme Mimetic Activities Of Ceonpmentioning
confidence: 99%
“…Furthermore, based on this property the group developed a facile colorimetric method for glucose detection. 45 The peroxidase-like activity provides CeONP broad potential applications in environmental chemistry, biotechnology and medicine.…”
Section: Nitric Oxide Radical Scavengingmentioning
confidence: 99%
“…The utilization of nanoceria as oxidase under some special circumstances was also reported. Recently, nanoceria have been used for several applications either in biotic conditions or abiotic conditions, such as antioxidants, [63][64][65] capping [36] and neuroprotection agents, [66][67][68][69][70][71][72] biosensors, [23,28,73] immunoassays, [31,32,74] color indicator [27,[75][76][77][78][79] and so on.…”
Section: Bio-application Prospects Of Nanoceria As Enzyme Mimeticsmentioning
confidence: 99%
“…Previous studies demonstrated that nanoceria possessed enzyme-like catalytic activity and were stable over a wide range of pH values and temperatures compared with natural enzyme horseradish peroxidase. [27,28] One of our ongoing works implies that activated nanoceria could maintain their catalytic activity at a higher level than native SOD at harsh pH and temperature conditions. Therefore, nanoceria present a promising enzyme mimetics for future applications.…”
Section: Parameters Influencing the Enzyme Mimetic Activities Of Nanomentioning
confidence: 99%
See 1 more Smart Citation